Questions of Interpretation of Certain Preconditions for Criminal Sanctions Against Legal Persons - Vajda, Szabolcs (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
In this study, the author analyses the conditions for the application of criminal law measures against legal persons. Despite the fact that legal persons are often involved in criminal activities, relatively few legal persons are actually prosecuted. One possible reason for this, according to the author, is that Act CIV of 2001 on criminal measures against legal persons (CMALP Act) sets out a wide range of conditions for a legal person to be subject to criminal measures. In the present study, the author provides a practical analysis of each of these conditions, covering the scope of the CMALP Act and the conditions explicitly mentioned in the CMALP Act.